Implementation and tests of FPGA-embedded PowerPC in the control system of the ATLAS IBL ROD card - Balbi, Gabriele; Bindi, M.; Falchieri, D.; Furini, M.; Gabrielli, A.; Kugel, Andreas; Travaglini, R.; Wensing, M. (Journal of Instrumentation, 2013)
The Insertable B-layer project is planned for the upgrade of the ATLAS experiment at LHC. A silicon layer will be inserted into the existing Pixel Detector together with new electronics. The readout off-detector system is implemented with a Back-Of-Crate module implementing I/O functionality and a Readout-Driver card (ROD) for data processing. The ROD hosts the electronics devoted to control operations implemented both with a back-compatible solution (using a Digital Signal Processor) and with a PowerPC embedded into an FPGA. In this document major firmware and software achievements concerning the PowerPC implementation, tested on ROD prototypes, will be reported.